What contributes to disability in progressive MS? A brain and cervical cord-matched quantitative MRI study - Tur, Carmen; Battiston, Marco; Yiannakas, Marios C; Collorone, Sara; Calvi, Alberto; Prados, Ferran; Kanber, Baris; Grussu, Francesco; Ricciardi, Antonio; Pajak, Patrizia; Martinelli, Daniele; Schneider, Torben; et al. (Multiple sclerosis, 2024)
We assessed the ability of a brain-and-cord-matched quantitative magnetic resonance imaging (qMRI) protocol to differentiate patients with progressive multiple sclerosis (PMS) from controls, in terms of normal-appearing (NA) tissue abnormalities, and explain disability. A total of 27 patients and 16 controls were assessed on the Expanded Disability Status Scale (EDSS), 25-foot timed walk (TWT), 9-hole peg (9HPT) and symbol digit modalities (SDMT) tests. All underwent 3T brain and (C2-C3) cord structural imaging and qMRI (relaxometry, quantitative magnetisation transfer, multi-shell diffusion-weighted imaging), using a fast brain-and-cord-matched protocol with brain-and-cord-unified imaging readouts. Lesion and NA-tissue volumes and qMRI metrics reflecting demyelination and axonal loss were obtained. Random forest analyses identified the most relevant volumetric/qMRI measures to clinical outcomes. Confounder-adjusted linear regression estimated the actual MRI-clinical associations. Several qMRI/volumetric differences between patients and controls were observed ( < 0.01). Higher NA-deep grey matter quantitative-T1 (EDSS: beta = 7.96, = 0.006; 9HPT: beta = -0.09, = 0.004), higher NA-white matter orientation dispersion index (TWT: beta = -3.21, = 0.005; SDMT: beta = -847.10, < 0.001), lower whole-cord bound pool fraction (9HPT: beta = 0.79, = 0.001) and higher NA-cortical grey matter quantitative-T1 (SDMT = -94.31, < 0.001) emerged as particularly relevant predictors of greater disability. Fast brain-and-cord-matched qMRI protocols are feasible and identify demyelination - combined with other mechanisms - as key for disability accumulation in PMS.